Pancasila as the Basis of the State - Alya Fitria Nida; Diah Wening Rizky; Revan Ramadhani; Riska Andi Fitriono (CV. Rayyan Dwi Bharata, 2022)
Pancasila is the basis of the state or commonly referred to as the Ideology of the Unitary State of the Republic of Indonesia. Pancasila is the legal basis in the implementation of state and national life. Pancasila is a guideline for norms that regulate life both in terms of economic, social, legal culture, education and others. Pancasila as the basis of the state means that every item of Pancasila values is a foundation in the state as an Indonesian citizen and is a guideline in living daily life in order to create an alignment of values and norms according to the teachings of Pancasila as the basis of the state.